ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Nur Hidayah; Rasiman Rasiman, Prastomo Budiargo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aim of this research is to investigate how students' mathematical problem solving abilities are related to the material on three-variable linear equation systems. This research is descriptive qualitative research. The research subjects were 3 class X students, 1 student with high cognitive abilities, 1 student with moderate cognitive abilities, and 1 student with low cognitive abilities. Research data was obtained through giving tests of mathematical problem solving abilities in the form of essay questions. Based on research, students with high cognitive abilities have good problem solving abilities starting with understanding the problem, planning strategies, implementing strategies, and checking back on the answers obtained. Students with moderate and low cognitive abilities do not have good problem solving abilities, students with moderate cognitive abilities are able to understand problems but are not precise in planning, implementing strategies and checking the answers obtained, and for students with low cognitive abilities not yet able to understand the questions, plan strategies, implement strategies or recheck the results of the answers obtained.